The Support Educational Commitee Participation in the Pedagogical Approach of an Educational Integration - Angélica Fontana-Hernández; Karla Durán-Chacón; Viviana Martínez-Ramírez; Viviana Rojas-Molina; Adriana Vargas-Navarro (Revista Electrónica Educare)
Educational services are essential to social and economical development of people, mainly to the progress of all sectors of society. Establishing actions that can promote the participation of various social groups is essential to improve their quality of life and building more respectful and fair human rights without any discrimination or exclusion.